2008
DOI: 10.1073/pnas.0803564105
|View full text |Cite
|
Sign up to set email alerts
|

Coal burning leaves toxic heavy metal legacy in the Arctic

Abstract: Toxic heavy metals emitted by industrial activities in the midlatitudes are transported through the atmosphere and deposited in the polar regions; bioconcentration and biomagnification in the food chain mean that even low levels of atmospheric deposition may threaten human health and Arctic ecosystems. Little is known about sources and long-term trends of most heavy metals before Ϸ1980, when modern measurements began, although heavymetal pollution in the Arctic was widespread during recent decades. Lacking det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
264
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 286 publications
(274 citation statements)
references
References 29 publications
9
264
0
1
Order By: Relevance
“…Another study of thallium, cadmium, and lead atmospheric deposition in Greenland ice core indicated that coal burning in North America and Europe was the source of these metals in the Arctic by the early 1900s, to the extent of two to fi ve times higher deposition than during recent decades. Although these results show substantially lower heavy-metal pollution in the North Atlantic sector of the Arctic than a century ago, contamination of other sectors may be increasing because of the rapid coal-driven growth of Asian economies (9).…”
Section: Thallium Is Included In Us Environmental Protectionmentioning
confidence: 56%
“…Another study of thallium, cadmium, and lead atmospheric deposition in Greenland ice core indicated that coal burning in North America and Europe was the source of these metals in the Arctic by the early 1900s, to the extent of two to fi ve times higher deposition than during recent decades. Although these results show substantially lower heavy-metal pollution in the North Atlantic sector of the Arctic than a century ago, contamination of other sectors may be increasing because of the rapid coal-driven growth of Asian economies (9).…”
Section: Thallium Is Included In Us Environmental Protectionmentioning
confidence: 56%
“…Four continuous BC ice core records covering ca. 1750 to 2013 have been published from Greenland (McConnell et al, 2007;McConnell and Edwards, 2008;McConnell, 2010;Keegan et al, 2014) and one 300-year record (1700 to 2004) from Svalbard (Ruppel et al, 2014). The high-elevation Greenland records indicate a BC deposition peak around 1910 followed by rapidly decreasing deposition until 1950 and more or less stable, almost preindustrial values until the present (McConnell, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The core was measured and weighed onsite, packed in plastic tubing, and shipped frozen in insulated boxes to the Desert Research Institute (DRI) in Reno, Nevada. The core was analyzed in July 2011 using a 5 well-established continuous ice core analytical system (McConnell et al, 2007;McConnell and Edwards, 2008). …”
Section: Ice Core Analysismentioning
confidence: 99%
“…The primary elemental and chemical source tracers presented here are black carbon (BC), excess lead (exPb), and non-sea-salt sulfur (nssS) (Figure 1d-f + as a biomass burning indicator (Fuhrer et al, 1996;Zennaro et al, 2014), and Tl for continental dust and coal (McConnell and Edwards, 2008). Previous work shows that during the pre-industrial era, BC at Summit derived almost entirely from biomass burning emissions, exPb from dust and forest fires, and nssS from marine biogenic emissions and volcanism (McConnell et al, 2007).…”
Section: No3mentioning
confidence: 99%